Piratería en el Golfo de Guinea: Respuestas desde la Unión Europea - Morales Morales, Rafael (Archivos de criminología, seguridad privada y criminalística, 2020)
Maritime piracy is not a new phenomenon in the history of mankind... there is extensive documentation that explains how and under what circumstances Julius Caesar was kidnapped by pirates in the Mediterranean Sea. It has always been a phenomenon feared by coastal population and settlements and, with the passing of time and the improvement of ships navigability conditions, by the crews of vessels sailing the seas. Besides, it has always been a real threat to commercial transactions and to the economic safety of those who have been involved, in one way or another, in the marine routes and of the countries that have bordered the waters. Modern history has added other problems to the phenomenon: the political destructuring of seaside countries, globalization and problems derived from political and economic issues. To provide solutions to the piracy phenomenon, global responses have been sought, including those of the European Union with very specific actions, such as the EU PROJECT Critical Maritime Routes Gulf of Guinea (CRIMGO) or the EU Strategy on the Gulf of Guinea and the Gulf of Guinea action plan 2015-2020.